A RARE CASE: PRIMARY MUCINOUS CYSTIC NEOPLASM OF THE GALLBLADDER - Halil İbrahim Taşcı; Özgür Hilal Erinanç; Emin Türk; Erdal Karagülle (İstanbul Tıp Fakültesi Dergisi)
Cystic lesions originating from the gallbladder are very rare. Mucinous cystic neoplasms of the liver and biliary system principally occur in the liver, followed by the extrahepatic biliary system. Only a few case reports were reported primarily in the gallbladder. A 63-year-old woman was admitted to our hospital with complaints of pain in the right upper abdomen, increasing after meals, and abdominal discomfort. A laparoscopic cholecystectomy was performed. Macroscopically, the cyst was localized in the serosa of the fundus. Based on immunohistochemical examination, the cyst was diagnosed as primary mucinous cystic neoplasia of the gallbladder. Although it is very rare, mucinous cystic neoplasia should be kept in mind when dealing with cystic lesions of the gallbladder. Due to serious associated problems such as the risk of malignant transformation or bile duct obstruction, particularly in larger cysts, a cholecystectomy is mandatory